Estudo químico e biológico de Conyza bonariensis (L.) Cronquist (Asteraceae) - Favila, Miguel Antonio Correa (2006)
Conyza bonariensis (L.) is a native plant of South America, easily found in the south area. It s popular name is buva or margaridinha-do-campo. This plant is very used in folk medicine for rheumatism, gout, cystitis, nephrite, dysmenorrhea, tooth pain, headache. The main secondary metabolits present in the species Conyza bonariensis (L.) were flavonoids, saponins, organics acids, cardyotonic and phenols. In the volatile oil of the var. bonariensis two major constituents were identified, the ester cis-lachnophyllum methyl (78,69%) and ester matricaria methyl (17,67%) present in the roots, and the components cis-lachnophyllum methyl ester (44,31%) and the caryophyllene oxide (22,0%) present in the leaves. In the var. microcephala, the major constituents found in the root were the ester cis-lachnophyllum methyl (88,87%), and in the leaves the ester trans-lachnophyllum methyl (43,05%). The volatile oils of the var. bonariensis displayed antimicrobial activity against microorganisms Klebsiella pneumoniae, Escherichia coli, Candida albicans Saccharomyces cerevisiae. The plant didn't demonstrate acute oral toxicity, in the concentrations 250,500,1000 and 2000 mg/kg in mice. The ethyl acetate and buthanol fractions exhibided a significative antioxidant activity by DPPH and β-carotene method in the concentration of 62,5 μg/ml. The crude extract and the buthanol fraction expressed larger cytotoxic activity with CL50 27,35μg/ml, as the volatile oil of the roots of the var. bonariensis CL50 0,48μg/ml against Artemia salina. Thus, the present work aimed at contributing to the studies of the native herbs of the state of Rio Grande do Sul.